2020
DOI: 10.1021/acs.jpcc.0c09313
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Particle Size and Phase Purity of “Single-Crystal” LiNi0.5Mn1.5O4 in Molten-Salt-Assisted Synthesis

Abstract: Spinel-structured lithium nickel manganese oxide (LiNi0.5Mn1.5O4, LNMO) is a low-cost battery cathode material with a high operating voltage (∼4.7 V vs Li+/Li), relatively high capacity (∼147 mA h g–1), and good rate performance. Previous studies have suggested that large particle size, single-crystal-like morphology, and high phase purity are favorable for achieving good electrochemical performance. However, simultaneous control over these properties is difficult for conventional solid-state synthesis at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The granules samples show extended surface regions which appear brighter in the SEM images. As already confirmed by energy-dispersive X-ray spectroscopy, [26,34] these areas can be attributed to secondary phases, which have a higher density due to the higher M:O ratio of 1:1 compared to 3:4 for the LNMO phase (rocksalt Li 0.3 Ni 0.2 Mn 0.5 O ρ = 5.4 g cm −3 [22] versus spinel LiNi 0.5 Mn 1.5 O 4 ρ = 4.45 g cm −3 [15] ). The octahedral LNMO primary particles of sample 4 show additional damage.…”
Section: Particle Morphologysupporting
confidence: 62%
“…The granules samples show extended surface regions which appear brighter in the SEM images. As already confirmed by energy-dispersive X-ray spectroscopy, [26,34] these areas can be attributed to secondary phases, which have a higher density due to the higher M:O ratio of 1:1 compared to 3:4 for the LNMO phase (rocksalt Li 0.3 Ni 0.2 Mn 0.5 O ρ = 5.4 g cm −3 [22] versus spinel LiNi 0.5 Mn 1.5 O 4 ρ = 4.45 g cm −3 [15] ). The octahedral LNMO primary particles of sample 4 show additional damage.…”
Section: Particle Morphologysupporting
confidence: 62%
“…However, compared with the LNMO sample, the intensities of bonds at 636, 494, and 402 cm –1 in the LNMO-F sample are increased, while that in the LNMO-Al sample are decreased. It is reported that the material with high electronic conductivity would reduce the peak intensity of Raman spectra. As is known to all, the disordered Fd 3 m structure in LNMO exhibits high electronic conductivity and lithium-ion conductivity . It is undeniable that the coexistence of two space group structures has been reported in the literature .…”
Section: Resultsmentioning
confidence: 97%
“…Next-generation batteries pursue high performance and environmental friendliness . The spinel LiMn 1.5 Ni 0.5 O 4 (LMNO) is a potential alternative cathode material because of the its high operating voltage of 4.8 V and it is cost-effective. …”
Section: Introductionmentioning
confidence: 99%